2017
DOI: 10.3892/br.2017.946
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of magnifying blue laser imaging and magnifying narrow-band imaging system for endoscopic diagnosis of Helicobacter pylori infection

Abstract: Abstract.Helicobacter pylori (Hp) infection is a major cause of gastric cancer. The use of proton-pump inhibitors, anti-platelet and anti-coagulant has become widespread in the clinic. Thus, it would be clinically useful to distinguish Hp-positive stomachs by endoscopic findings alone. Blue laser imaging (BLI) is a new image-enhanced endoscopy technique that utilizes a laser light source developed for narrow-band light observation. We investigated the diagnostic ability of magnifying BLI endoscopy to distingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, it is also useful for distinguishing H. pylori-related gastritis, as is magnifying NBI (M-NBI). M-BLI endoscopy has potential diagnostic performance for H. pylori-related gastritis with a sensitivity of 98% and a specificity of 92% (Tomomitsu Tahara et al, 2017), as is demonstrated in Figure 7. Endoscopic Diagnosis for H. pylori Infection: White Light Imaging (WLI)…”
Section: Blimentioning
confidence: 99%
“…Moreover, it is also useful for distinguishing H. pylori-related gastritis, as is magnifying NBI (M-NBI). M-BLI endoscopy has potential diagnostic performance for H. pylori-related gastritis with a sensitivity of 98% and a specificity of 92% (Tomomitsu Tahara et al, 2017), as is demonstrated in Figure 7. Endoscopic Diagnosis for H. pylori Infection: White Light Imaging (WLI)…”
Section: Blimentioning
confidence: 99%